Efficacy of vibration exercise as a warm-up modality for overground sprinting - Moodie, V.; Benson, A. C.; Gordon, B. A.; Lythgo, N. (International Journal of Exercise Science, 2015)
This study investigated the efficacy of vibration exercise (VbX) as a warm-up modality for maximal overground sprinting. Ten national level sprinters participated in a randomized crossover design (14.0 ± 7.4 days washout period). A VbX warm-up was compared to a warm-up involving sprint-specific exercises (control condition). The VbX warm-up involved 10 ´ 1 minute bouts delivered by a Galileo 900 side-alternating plate (frequency = 26 Hz, peak-to-peak displacement = 9 mm) with 30 s rest between bouts (total time = 15 minutes). The sprint-specific warm-up involved jogging, dynamic exercises and sprinting drills followed by 3 ´ 40 m sub-maximal sprints not exceeding 95% of maximal speed over a 15 minute period. After each warm-up (within 2 minutes), 6 ´ 40 m maximum sprints were completed from a crouch start position with starting blocks. Outcome measures were recorded by timing gates (Swift Performance, Australia) and a Vicon Motion Measurement System (Oxford, UK). Measures recorded were sprint time over the 0-4 m, 5-10 m, 10-20 m, 20-40 m and 5-40 m intervals. The stride length, stride velocity and stride time of both legs were recorded over the 0-4 m interval by the Vicon system. All measures remained unchanged across warm-up modalities. It is reasonable to conclude that VbX may be used as an alternative warm-up for sprinting over 40 m. Given its time efficiency and suggested relatively low metabolic cost, VbX may be a suitable warm-up for activities requiring multiple sprints over a competition day or game period.